Leading the learning revolution the expert's guide to capitalizing on the exploding lifelong education market - Cobb, Jeff (New York AMACOM, 2013)
Explains how to get involved in the continuing adult education industry, covering such topics as creating business models for the online learning landscape, promoting content, creating an action plan, and converting prospects to customers.
Your opportunity, should you choose to accept it -- The new learning landscape -- Finding and understanding your lifelong market -- Business models for the new learning landscape -- Standing out and delivering value -- Learning by design -- Tools and competencies -- Cultivating the content-context habit -- Promoting and converting -- The best laid plans: executing, measuring, innovating -- Taking it to the next level: leading learning -- Creating an action plan.
Includes bibliograhical references and index.
Keywords: Continuing education -- Marketing; Adult education -- Marketing; Education and training services industry